ANALISIS KADAR ALBUMIN IKAN SIDAT (Anguilla marmorata dan Anguilla bicolor) DAN UJI AKTIVITAS PENYEMBUHAN LUKA TERBUKA PADA KELINCI (Oryctolagus cuniculus) - Ariza Abu Bakar Putri; Yuliet Yuliet; Jamaluddin Jamaluddin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
Eel is one kind of fish which contain albumin. Albumin is useful in the formation of new body tissue during growth and can accelerate the healing of body tissue. This study aimed to determine levels of albumin in the eels (Anguilla marmorata and Anguilla bicolor) as well as its effect of open wound healing tested at various concentrations. The albumin levels were determined using Bromocresol green method with three times repetition. The results showed that average albumin levels of Anguilla marmorata was 13,269 mg/100 g and Anguilla bicolor was 8,998 mg/100 g. Eel extract with the highest level of albumin was continued to pharmacological tests using 5 rabbits which had been open-wounded in 5 areas. Each rabbit was then given 5 treatments. The first two rabbits got positive control containing povidone iodine and negative control (ointment base), while the other three got albumin extract successively at concentration of 5%, 10% and 15%. The wounds were observed on days 1, 3, 5, 7, 10, 12, and 14. The data analysis for albumin levels was done using Independent T test and for open wound healing percentage using One Way ANOVA. The analysis results showed a significant difference of albumin levels between Anguilla marmorata and Anguilla bicolor and it found that the highest level of albumin was in Anguilla marmorata species. The effective extract concentration of albumin in wound healing was at concentration of 5% with wound healing percentage of up to 100%